Test of Anti-Inflammatory Activity of 70% Ethanol Extract of Binahong Leaves (Anredera cordifolia) in Male White Rats (Rattus norvegicus) Induced with Carrageenan - Marsanda Dara Paquita Imani; Wima anggitasari; Dhina Susanti (LPPM Universitas dr. Soebandi, 2024)
Inflammation is a protective response to tissue damage due to physical trauma. Steroid treatment can reduce prostaglandin release but often increases the risk of diabetes as a side effect. NSAIDs can address inflammation by inhibiting COX-1 and COX-2 enzymes, but may cause gastrointestinal damage. Therefore, there is a need for traditional and natural medicine alternatives that can stabilize free radicals and prevent cell damage, such as the binahong plant. This plant contains flavonoid compounds with high antioxidant properties, which can neutralize free radicals.This study aims to determine the anti-inflammatory activity of 70% ethanol extract of binahong leaves (Anredera cordifolia) in male white rats (Rattus norvegicus) induced with carrageenan. This study employs a laboratory experimental design with 20 test animals divided into 4 treatment groups, with extraction performed using the maceration method. In the screening test, a tube method is used, and anti-inflammatory testing is conducted by observing changes in the volume of rat paws before and after carrageenan injection. Data processing and analysis are performed using ANOVA in SPSS software. The percentage of edema was found to be 7.41% for the 200 mg/kg BB dose, 6.98% for the 400 mg/kg BB dose, 7.60% for the positive control, and 19.76% for the negative control. Normality and homogeneity tests showed normal and homogeneous results. ANOVA results indicated no significant differences, while LSD tests showed significant differences between the negative control and all treatment groups. Screening results (+) indicated the presence of flavonoid compounds.The ethanol extract of binahong leaves has anti-inflammatory activity as evidenced by the percentage of edema (7.41% and 6.98%) in male white rats induced with carrageenan. The most effective extract dosage is 200 mg/kg BB. Keywords: Anti-inflammatory, Binahong Leaves, Carrageenan, Anredera cordifolia